A Comparative Study of the Marketing Strategies of Author Tere Liye and Other Indonesian Authors in the Book Industry - Agustinus Miranda Wijaya; Mutiara Ramadhani; Erwin Permana (Dinasti International Journal of Education Management and Social Science, 2026)
This study aims to analyze the marketing strategy implemented by Tere Liye and compare it with the conventional marketing model commonly used by Indonesian authors through publishing houses. The research uses a descriptive approach based on literature analysis and secondary data related to digital transformation in the publishing industry. The results show that the marketing strategy adopted by Tere Liye reflects a shift from a conventional publishing model to a digital-based direct-to-consumer approach through his own e-commerce platform. This strategy allows greater control over pricing, promotion, and distribution. In contrast, most Indonesian authors generally rely on publishers and bookstores for distribution, where marketing control is largely handled by third parties. The findings indicate that Tere Liye’s strategy offers several advantages, including full control over pricing and promotional activities, more direct and intensive relationships with readers, and the potential for higher profit margins due to a shorter distribution chain. However, this model also presents certain challenges, such as relatively limited distribution reach and the need for independent management of operational and logistical processes. On the other hand, the conventional strategy used by authors through publishers provides advantages in terms of wider distribution networks and established publishing systems. Nevertheless, this approach also has limitations, including reduced author control over pricing and promotion, as well as smaller profit margins due to the involvement of multiple intermediaries in the distribution process. Overall, the study highlights the importance of flexible business models in the publishing industry to remain competitive amid ongoing digital transformation.